Nurse Strategies to Improve the Quality of Psychosocial Care During the COVID-19 Pandemic - Jesika Pasaribu; Budi A. Keliat; Novy H. C. Daulima; Kristina Lisum; Gipta G. Widodo (Wolters Kluwer Medknow Publications, 2024)
Background: Nurses play a critical role in combating the COVID-19 pandemic, facing numerous challenges in providing care to COVID-19 patients, particularly addressing their psychological issues. This study aims to explore nurses' experiences in overcoming care challenges and enhancing nursing strategies. The study was held in Indonesia. Materials and Methods: Primary nurses and nurse managers responsible for COVID-19 patient care were interviewed extensively for data collection. The Collaizi method was used for data processing. Results: The study identified three key themes: psychosocial nursing interventions, addressing obstacles in psychosocial care, and enhancing the quality of psychosocial nursing care. Conclusions: Comprehensive nursing care proves effective in addressing the psychosocial challenges faced by COVID-19 patients.